Non-nutritive Sweeteners Induce Hypothalamic ER Stress Causing Abnormal Axon Outgrowth - Park, Soyoung; Sethi, Sunjay; Bouret, Sebastien G. (Frontiers in Endocrinology, 2019)
With the prevalence of obesity, non-nutritive sweeteners (NNS) have been widely used as sugar substitutes as they deliver a sweet taste without excessive caloric load. However, it is increasingly recognized that NNS are not inert compounds and may cause long-term metabolic perturbations. Endoplasmic reticulum (ER) stress has emerged as a critical link in the development of obesity and type 2 diabetes. In this study, we investigated the effects of NNS found in common diet beverages (i.e., sucralose, aspartame, acesulfame potassium) and a natural sweetener (i.e., rebaudioside A) on ER stress in the hypothalamic cell line mHypoE-N43/5 in vivo and on axonal outgrowth ex vivo. Sucralose, aspartame, and acesulfame potassium caused elevated ER stress gene expression in mHypoE-N43/5 cells, with sucralose and acesulfame potassium having the most potent effect. Moreover, acesulfame potassium treatment reduced axon outgrowth from arcuate nucleus explants and this effect was attenuated with the ER stress-relieving drug tauroursodeoxycholic acid. Furthermore, sucralose induced cytotoxicity and acesulfame potassium increases caspase3/7 activity at high concentrations in mHypoE-N43/5 cells. In contrast, rebaudioside A only had moderate effects on hypothalamic ER stress and no adverse effects on axon outgrowth, cytotoxicity, or caspase3/7 activity. Together, our data reveal that commonly consumed NNS cause cellular stress in hypothalamic cells disrupting axon outgrowth and that these biological alterations are not seen with rebaudioside A. These data provide biological plausibility for some NNS to adversely impact metabolic health and identifies rebaudioside A as a sweetener with lower detrimental biological impact on hypothalamic cells.